PENGARUH VARIETAS DAN JARAK TANAM TERHADAP KUALITAS BENIH UMBI BAWANG MERAH SELAMA PENYIMPANAN - Rajiman Rajiman; S. Megawati; I.M P Adiwijaya; N.D Permata (Percetakan Umi Toaha Makassar, 2023)
This study aims to determine the effect of variety and plant space on shallots seeds quality during storage. The study used a factorial complete randomized block design with 5 replications. The first factor was Variety (V), consisting of V1 = Tajuk, V2 = Crok Kuning, and V3 = Srikayang. The second factor was the plant spacing (J) consisting of J1 = 15cm x 15 cm, J2 = 15 cm x 20 cm, J3 = 20 cm x 20 cm, and J4 = 25cm x 20 cm. The results showed that the use of varieties significantly affects weight loss, germination and vigor. Varieties of Tajuk produce the lowest weight loss, germination and vigor. The crop spacing had a significant effect on weight loss at 3 months, germination of 1 and 3 months, but had no significant effect on 1 and 2 months weight loss and 1-3 months of germination, 2 months of vigor